GEDSI Principles in Islamic Early Childhood Education: Evidence from a Muslim Minority Community on Rote Island, Indonesia - Ramadoni; Fitriyah, Fifi Khoirul; M. Zainudin; Mustofa; Kozin, Wakhid; Kartiko, Ari (Jurnal Pendidikan Agama Islam, 2026)
Purpose – This study explores teachers’ perceptions of the importance and implementation of Gender Equality, Disability, and Social Inclusion (GEDSI)-aligned practices in Islamic early childhood education within a remote Muslim minority context. Design/methodology/approach – A descriptive exploratory survey was conducted involving all five teachers from the only two Islamic early childhood education institutions on Rote Island, Indonesia. Data were collected using a structured questionnaire and analyzed descriptively using Importance–Performance Analysis (IPA). The instrument showed moderate internal consistency (Cronbach’s α = .625). Findings – Teachers generally reported high levels of both perceived importance and self-reported implementation across the GEDSI dimensions. Although several indicators showed relatively larger importance–performance differences than others, the overall pattern was characterized by consistently high ratings with limited variability. These findings provide preliminary descriptive evidence of perceived alignment between GEDSI principles and classroom practices while highlighting the need for additional observational and qualitative evidence to better understand implementation processes. Research implications/limitations – The small population, self-reported data, moderate reliability, and possible ceiling effects limit interpretation of the findings. Future studies should involve larger samples, validated instruments, and multiple data sources to strengthen evidence on GEDSI implementation. Originality/value – This study provides preliminary evidence from a geographically isolated Muslim minority context and highlights both the feasibility and methodological challenges of applying IPA to examine perceived GEDSI implementation in Islamic early childhood education.